The Effect of E-Commerce Platform on Inventory Turnover: Evidence from Indonesian Retail Companies - Nina Mellyana; Taufik Faturohman (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
Digital transformation has transformed the retail industry, as consumers gradually shift from physical stores to online shopping platform. This condition has intensified competition and encouraged retail companies to adopt online channel. This study examines the effect of e-commerce platform adoption and other factors, such as gross margin, capital intensity, sales growth, firm size, and time trend, on inventory turnover among retail companies in Indonesia. The study objective is to examine whether adopting e-commerce actually has a positive effect on inventory turnover. A quantitative method is applied using secondary financial statement data from 14 retail companies covering the years 2016 to 2024. The study using panel data regression with the random effects model. The results show that e-commerce platform adoption has an insignificant effect, suggesting that e-commerce adoption alone does not directly enhance inventory efficiency in Indonesian retail companies. This study also find that gross margin has a significant negative effect on inventory turnover, while sales growth has a significant positive effect. Capital intensity, firm size, and time trend has no significant influence. Overall, this study provides new insights into how the use of e-commerce platform affects inventory turnover in the Indonesian retail industry.